N -Glycan–dependent protein folding and endoplasmic reticulum retention regulate GPI-anchor processing - Liu, Yi-Shi; Guo, Xin-Yu; Hirata, Tetsuya; Rong, Yao; Motooka, Daisuke; Kitajima, Toshihiko; Murakami, Yoshiko; Gao, Xiao-Dong; Nakamura, Shota; Kinoshita, Taroh; Fujita, Morihisa (The Journal of cell biology, 2018)
Glycosylphosphatidylinositol (GPI) anchoring of proteins is a conserved posttranslational modification in the endoplasmic reticulum (ER). Soon after GPI is attached, an acyl chain on the GPI inositol is removed by post-GPI attachment to proteins 1 (PGAP1), a GPI-inositol deacylase. This is crucial for switching GPI-anchored proteins (GPI-APs) from protein folding to transport states. We performed haploid genetic screens to identify factors regulating GPI-inositol deacylation, identifying seven genes. In particular, calnexin cycle impairment caused inefficient GPI-inositol deacylation. Calnexin was specifically associated with GPI-APs, dependent on N-glycan and GPI moieties, and assisted efficient GPI-inositol deacylation by PGAP1. Under chronic ER stress caused by misfolded GPI-APs, inositol-acylated GPI-APs were exposed on the cell surface. These results indicated that N-glycans participate in quality control and temporal ER retention of GPI-APs, ensuring their correct folding and GPI processing before exiting from the ER. Once the system is disrupted by ER stress, unprocessed GPI-APs become exposed on the cell surface.